Artificial infiltration in drinking water production: Addressing chemical hazards using effect-based methods. (1st August 2022) - Yu, Maria; Mapuskar, Shreya; Lavonen, Elin; Oskarsson, Agneta; McCleaf, Philip; Lundqvist, Johan
Highlights: Very few effect-based studies done on artificially-infiltrated drinking water sources. Contamination of artificially-infiltrated groundwater can occur. Arylhydrocarbon receptor activation most prevalent in raw water before infiltration. Here, bioactivities from chemical hazards were reduced following artificial infiltration. Abstract: Artificial infiltration is an established managed aquifer recharge method that is commonly incorporated into drinking water processes. However, groundwater sourced from this type of purification method is prone to contamination with chemical hazards. Such an instance was previously shown at a Swedish DWTP where the river water was contaminated by hazardous chemicals during artificial infiltration. Further, there remains a paucity of research studying the quality of drinking water following this type of treatment from an effect-based bioanalytical perspective. In the current study, an effect-based assessment for chemical hazards was conducted for a Swedish drinking water system comprised of two DWTPs fed artificially-infiltrated river water. In this system, artificial infiltration of the river water takes approximately six to eight months. A sampling event was conducted in the autumn season and the samples were enriched by solid phase extraction. A panel of cell-based reporter gene assays representing several toxicity pathways was selected: oxidative stress response (Nrf2 activity), aryl hydrocarbon receptor (AhR) activation, and hormone receptor-mediated effects (estrogen receptor [ER], androgen receptor [AR]). AhR and ER bioactivities were detected in samples collected from the river intake and in the open-air infiltration basins prior to artificial infiltration. However, the AhR activity decreased and ER activity was effectively removed following artificial infiltration. In the Nrf2 and AR assays, no bioactivities above cut-off levels were detected in any samples collected along the entire treatment process of the drinking water production from source to tap. Using a suite of bioassays, the current study highlighted the effectiveness of artificial infiltration in reducing bioactive compounds in this raw river water. Although artificial infiltration is a common purification method in drinking water production, the limited number of effect-based studies evaluating the effectiveness of this method emphasizes the need for further research to better understand the risks and benefits of this water treatment process. Graphical abstract: Image, graphical abstract